Iridium complex immobilization on covalent organic framework for effective C—H borylation - Vardhan, Harsh; Pan, Yanxiong; Yang, Zhongyu; Verma, Gaurav; Nafady, Ayman; Al-Enizi, Abdullah M.; Alotaibi, Tawfiq M.; Almaghrabi, Omar A.; Ma, Shengqian (APL materials, 2019)
The strong coordination between metal ions and binding moieties in functional porous materials is central to the design and advancement of heterogeneous catalysis. In this study, we have successfully immobilized catalytically active iridium ions on a two-dimensional covalent organic framework (COF) having bipyridine moieties using a programmed synthetic procedure. The iridium immobilized framework, Ircod(I)@Py-2,2′-BPyPh COF, had high porosity, good stability, and exhibited excellent catalytic activity for C—H borylation, as compared with the pristine framework. Additionally, Ircod(I)@Py-2,2′-BPyPh COF was found to be an efficient catalyst for a series of electronically and sterically substituted substrates. The immobilized COF possessed excellent reusability, recyclability, and retention of crystallinity. This report highlights the role of porous materials as an ideal decorating platform for conducting a wide range of potent chemical conversions.